Specificity of translation of Japanese environmental laws - Ахaпов Е. А.; Ибрaгимовa А. А. (Journal of Oriental Studies, 2018)
The real work is devoted to features of the translation of the ecological text. In the world constantly there are various changes affecting everything aspects of life, especially the last decades the ecology has undergone considerable influences. We see how value of influence of the nature has grown today therefore also importance of understanding of ecological texts at people of the different countries and language groups, for the solution of the common, world problems grows. The translation of the ecological text, unlike the translation of fiction in which the translator is obliged to transfer art and esthetic advantages of the original differs in a form, language means a little, and also a pronounced communicative orientation. In particular, it is connected with the translation of concepts and designations, processes that causes urgent need in their high-quality translation.